Comparison of Arthroscopic Microfracture and Retrograde Subchondral Drilling in the Treatment of Osteochondral Lesions of Talus - Kasman, U. O; Korkmaz, Ö (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2024)
PURPOSE OF THE STUDY: In our study, it was aimed to evaluate the efficacy of microfracture and retrograde subchondral drilling on clinical outcomes in patients who underwent ankle arthroscopy due to osteochondral lesion of medial talus. MATERIAL AND METHODS: Twenty eight patients with osteochondral lesion of talus less than 1.5 cm2 treated with ankle arthroscopy were evaluated retrospectively. Microfracture was performed in 16 patients and retrograde subchondral drilling was performed in 12 patients that there was no loss of integrity in the cartilage layer or cartilage layer is partially preserved during ankle arthroscopy. Postoperative evaluations of the patients were done with Foot and Ankle Ability Measure (FAAM) and results of both group were compared statistically. RESULTS: The mean activities of daily living scale was 93.4±3.2 and sportive activity scale was 90.1±5.7 in the retrograde drilling group. In the micro-fracture group, mean activities of daily living scale was 93.8±4.1 and mean sportive activity scale was 88.9±9.5. No significant difference was found as a result of statistical comparisons of both groups results. DISCUSSION: It has been determined that the size and preservation of the integrity of talar osteochondral lesions are important factors on clinical results. Results of arthroscopic debridement, microfracture and drilization are not good in lesions larger than 1.5 cm2 and lesions with impaired integrity. In our study, depending on the general literature, osteochondral lesions in talus were less than 1.5 cm2 in patients who underwent arthroscopic micro fracture and retrograde drilling. CONCLUSIONS: Both microfracture and retrograde subchondral drilling are effective treatment methods with good clinical results for talar osteochondral lesions less than 1,5cm2 . Retrograde subchondral drilling can be an alternative treatment method with the reliability of clinical results in patients with no loss of the integrity of the cartilage layer or cartilage layer is partially preserved. KEY WORDS: talus, osteochondral lesion, microfracture, subchondral drilling.
Keywords: dospělí; hlezenní kloub; retrospektivní studie; Humans; Talus; Cartilage, Articular; Activities of Daily Living; artroplastika subchondrální; mužské pohlaví; Ankle Joint; Adult; výsledek terapie; talus; Treatment Outcome; ženské pohlaví; Arthroplasty, Subchondral; činnosti denního života; lidé; kloubní chrupavka; Retrospective Studies; artroskopie; Male; Arthroscopy; Female